Synthetic folic acid supplementation during pregnancy may increase the risk of developing autism - DeSoto, M. Catherine; Hitlan, Robert T. (Journal of Pediatric Biochemistry, 2012)
Persons in developed countries are getting large amounts of folates in the form of folic acid. Folates are now ingested in three ways: as natural folates from food, as synthetic folic acid added to processed grains, and synthetic vitamin supplements. As a result of the supplementation, the circulating level of unmetabolized folic acid as well as total folates has greatly increased over the past generation, probably to levels largely unprecedented in human history. Folic acid has been shown to be able to epigenetically alter the functioning of the genome and to have long term effects on gene expression. The Centers for Disease Control Vaccine Safety Datalink data set compared children with autism to control children on several variables. Here, we report that folic acid supplementation during gestation is associated with an increased risk for autism. The effect remains even when health seeking behaviors and other variables are controlled.
Keywords: Folic acid; excess vitamins; autism; folate; synthetic vitamins